Assessment of Practical Experience in the Development and Testing of Interactive Mobile Technology Elements - Takhsin, Muhammad; Afkar, Muhammad Agha (Journal Mobile Technologies (JMS), 2023)
The study aims to conduct a comprehensive assessment of practical experiences that emerge during the development and testing processes of interactive mobile technology elements. The primary focus examines challenges, successes, and learning outcomes that occur when applying interactive mobile technology in real-world scenarios. The research methodology includes detailed surveys of participants involved in developing and testing interactive mobile technology, along with thorough analysis of their experiences across multiple implementation phases. The research examines various aspects, including technology element effectiveness, alignment with development objectives, user interaction patterns, technical limitations, adaptation requirements, and potential positive or negative impacts during implementation. Research findings are expected to benefit developers, practitioners, and academics in designing and implementing interactive mobile technology through evidence-based recommendations. Additionally, the study helps guide further advancement in understanding interactive mobile technology potential across various fields, including education, teaching, professional training, healthcare applications, and industrial implementations. The assessment methodology provides a structured framework for evaluating practical experiences that can be applied to future technology development cycles.